2019
DOI: 10.48550/arxiv.1906.02899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards Non-I.I.D. Image Classification: A Dataset and Baselines

Abstract: I.I.D. 1 hypothesis between training and testing data is the basis of numerous image classification methods. Such property can hardly be guaranteed in practice where the Non-IIDness is common, causing instable performances of these models. In literature, however, the Non-I.I.D. 2 image classification problem is largely understudied. A key reason is lacking of a well-designed dataset to support related research. In this paper, we construct and release a Non-I.I.D. image dataset called NICO 3 , which uses contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…NICO: we evaluate the cat/dog classification in "Animal" dataset in NICO, a benchmark for non-i.i.d problem in He et al (2019). Each animal is associated with "grass","snow" contexts with different proportions, denoted as d s ∈ R 4 (cat,dog in grass,snow).…”
Section: Real-world Ood Challengementioning
confidence: 99%
See 1 more Smart Citation
“…NICO: we evaluate the cat/dog classification in "Animal" dataset in NICO, a benchmark for non-i.i.d problem in He et al (2019). Each animal is associated with "grass","snow" contexts with different proportions, denoted as d s ∈ R 4 (cat,dog in grass,snow).…”
Section: Real-world Ood Challengementioning
confidence: 99%
“…On NICO, we implement ConvNet with Batch Balancing as a specifically benchmark inHe et al (2019). The results are 60 ± 1 on m = 8 and 62.33 ± 3.06 on m = 14.…”
mentioning
confidence: 99%
“…First of all, we prefer to accurately and intuitively quantify the degree of distribution shift each dataset in the federated learning environment. Based on NI [5], we found that different datasets correspond to different trained feature extractors g ϕ (•) and classifiers f θ (•), and get the corresponding results in the NI equation. In the actual case of federal learning, we found that this equation is not practical and explored a simpler and clearer model to replace the model in the equation.…”
Section: Non-iid Equation Definitionmentioning
confidence: 99%
“…Based on the [5], we will represent the label of dataset image in two dimensions: main concept and contexts which provides a novel perspective on the classification of dataset images. For example, in CIFAR10 [10] dataset, in the category of 'dog', images are divided into different contexts such as 'grass', 'car', 'beach', meaning the 'dog' is on the grass, in the car, or on the beach respectively.…”
Section: Concept Shiftmentioning
confidence: 99%
See 1 more Smart Citation